2011
DOI: 10.1136/thoraxjnl-2011-201054c.92
|View full text |Cite
|
Sign up to set email alerts
|

P92 C reactive protein as a predictive indicator of treatment and disease progression in patients with sarcoidosis: a retrospective observational cohort study in the West of Ireland

Abstract: patient had polyclonal hypogammaglobulinaemia, but levels were not measured in 11/42 (26%) with potential features of CVID. Conclusion Our study identified a cohort of patients with a diagnosis of sarcoidosis and features associated with CVID. We found that immunoglobulins were not being routinely measured during the work-up of patients with sarcoidosis as recommended by the Map of Medicine. Recent review of 28 local CVID patients identified two who were initially misdiagnosed with sarcoidosis. In one case thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…None of the PFT indices at the time of manifestation of sarcoidosis was found to be a possible prognostic marker of disease course in our study. Unlike our study results, McDonnell et al in their retrospective observational study found that low DLCO at sarcoidosis presentation may identify patients without Löfgren's syndrome who are more likely to develop physiological progression [52]. However, other authors [23,53] did not confirm their findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…None of the PFT indices at the time of manifestation of sarcoidosis was found to be a possible prognostic marker of disease course in our study. Unlike our study results, McDonnell et al in their retrospective observational study found that low DLCO at sarcoidosis presentation may identify patients without Löfgren's syndrome who are more likely to develop physiological progression [52]. However, other authors [23,53] did not confirm their findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Other specific potential prognostic factors found in other studies, but not confirmed or not investigated in our study are older patients' age [23,53,54], C reactive protein [52], and extrapulmonary involvement of disease [7,53].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In this study, ACE had a greater correlation with lung function change after methotrexate therapy than sIL-2R [73]. CRP is a proinflammatory acute phase reactant elevated in chronic sarcoidosis, and elevated baseline values may correlate with disease severity, physiologic progression of disease, and treatment response [77,78]. CRP may be useful in monitoring disease activity but requires validation.…”
Section: Serum Biomarkersmentioning
confidence: 96%